(untitled) (Journal of the College of Basic Education, 2023)
This study sheds light on the follow-up of the Chinese and Soviet position towards the revolution in Dhofar.Especially the period between 1955 and 1975, and the events that took place during this period.and international and regional changes, due to the formation of the Popular Front for the Liberation of Oman and the Arab Gulf, and supportAnd support provided by the countries supporting the front, including China, the main financier of the front in 1968After achieving its goals and interests, it abandoned the front in 1972, and the Soviet Union took its place.as the main fund of the front.The support that was provided to the front from Western countries comes indirectly through Yemen. and attemptReinforcing the stages of the struggle in Dhofar, and the recent events and developments on the Popular Front for the Liberation ofDhofar and the Arabian Gulf, and learning about the positions of Western countries and the support provided by China and the European Union.the Soviet Union, and the accompanying events and developments that reflect the political, economic and social relationsbetween Oman and Western countries.